MENGEMBANGKAN NILAI-NILAI KARAKTER MELALUI PROSES PRODUKSI KULIAH DRAMA JURUSAN PENDIDIKAN BAHASA INGGRIS UNDIKSHA - Kadek Sonia Piscayanti (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2012)
This writing is aimed at describing how drama course can stimulate the development of character values. Theyare developed through the production stages of drama performance in the English Education Department. Thecharacter values are stimulated through the process of pre-production, production, and post- production. The character values which are shared are tolerance, discipline, hard work, democracy, and togetherness.Key words: drama course, character values, production stage, drama performance